Agronomic Optimal Plant Density by Yield Environment in Soybean - W. D. Carciochi; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2019)
This research report presents a summary of a peer-reviewed publication: Carciochi W.D.; Schwalbert R.; Andrade F.H.; Corassa G.M.; Carter P.; Gaspar A.P.; Schmidt J.; Ciampitti I.A. 2019. Soybean seed yield response to plant density by yield environment in North America. Agronomy Journal. Recent economic and productive circumstances have caused interest in within-field variation of the agronomic optimal plant density (AOPD) for soybean [Glycine max(L.) Merr.]. Thus, the objective of this study was to determine the AOPD by yield environment (YE) for soybean. During 2013 and 2014, nine site-years with a total of 78 yield-to-plant density responses were evaluated in different regions of the United States and Canada. A soybean database evaluating seeding rates ranging from 69,000–271,000 seeds/a was utilized, including the final number of plants and seed yield. The data were classified in YEs: low (LYE,<59.6 bu/a), medium (MYE, 59.6-64.1 bu/a), and high (HYE,>64.1 bu/a). The main outcomes for this study were: 1) AOPD decreased by 24% from LYE (127,000 plants/a) to HYE (97,000 plants/a); 2) greater AOPD in a LYE was not related to a low plant survival rate; and 3) cumulative precipitation during soybean reproductive growth period was 39% lower in LYE compared with MYE and HYE, possibly reducing its reproductive ability. This study presents the first attempt to investigate the seed yield-to-plant density relationship via understanding final plant establishment and by exploring the influence of weather defining soybean YEs in North America.
Keywords: plant establishment; weather conditions; variable seeding rate